Model Sistem Verifikasi Dokumen Ijazah Digital Berbasis Teknologi Blockchain - Alfina, Alfina; Syafrinal, Syafrinal (Universitas PGRI Kanjuruhan Malang, 2022)
Blockchain is an information recording system and cannot be modified, hacked, or cheated. Along with the development of new technologies, researchers hope blockchain technology will have the same impact on the world of education, especially in universities in Indonesia. From the results of this study, there will be a model of a diploma verification system based on blockchain technology. From the problems above, it is necessary to make a prototype that can see or detect the authenticity of a document, especially for diplomas at tertiary institutions in Indonesia. Namely by implementing blockchain technology as the latest innovation for the future of the Digital Diploma Document Verification System in Indonesia and the World. Specific research objectives include; 1) Designing computer vision-based tools to determine the identification of the authenticity of diploma documents, 2) Developing prototypes and testing functional programming to determine the level of suitability with field conditions, 3) Implementing blockchain and similar technologies for diploma identification in order to accelerate diploma identification. The research flow begins by inputting the main image of the STMIK Indonesia Banda Aceh certificate. Then it is described in the Blockchain format of five chains, where each chain tests using the Peak Signal to Noise Ratio (PSNR) method, and the highest value is an identical image. This study's results indicate identical images founds using the Block Chain format and the PSNR method.